Factors Affecting Efficiency of Smallholder Cocoa Farmers: A Tobit Model Application in Malaysia - Fadzim, Wan Roshidah; Aziz, Mukhriz Izraf Azman; Mat, Siti Hadijah Che; Maamor, Selamah (International Journal of Economics and Financial Issues, 2016)
The determinants technical efficiency among smallholder cocoa farmers has been well studied in agricultural literature. Among the factors identified are the demographic characteristics that affect farmers’ decision-making process and the ability of farmers to execute the decision effectively. In Malaysia, cocoa production is characterized by several problems that lead to low productivity. The low productivity has resulted in the continuous fall in percentage share of cocoa output since 2001. Accordingly, this study explores the determinants of technical efficiency among cocoa farmers in Malaysia. The study relies upon primary data gathered during the 2013 production season. Data are collected from a set of structured questionnaire administered on 375 smallholder cocoa farmers throughout Malaysia. Results of the analysis show that record keeping, level of knowledge and status of farmers (either part-time or full-time basis) affects efficiency. This finding suggests that policies that would directly affect these identified variables should be pursued. Keywords: Cocoa, technical efficiency, Tobit analysis JEL Classifications: D24, Q12